The correlation between ultrasonographic features, bFGF, and the local invasiveness of thyroid papillary carcinoma. Issue 26 (26th June 2020) - Jia, Zhi-Ying; Wu, Xiu-Lan; Zhang, Yin-Hua; Ma, Bin-Lin; Ma, Fu-Cheng
Abstract : Abstract: The present study aimed to investigate the correlation between ultrasonographic features, basic fibroblast growth factor (bFGF), and the local invasiveness of papillary thyroid carcinoma (PTC). A total of 350 samples of thyroid nodules were collected. Routine ultrasonography was performed before the operation and routine pathological diagnosis and bFGF detection were performed after the operation.' These 350 samples of thyroid nodules included 90 samples of nodular goiter, 36 samples of focal thyroiditis, and 224 samples of PTC. A total of 326 thyroid nodules were examined for bFGF. The results revealed that the difference in the expression of bFGF between the benign and malignant groups was statistically significant ( P < .05) and the difference in the positive expression of bFGF between the invasive and non-invasive PTC groups was statistically significant ( P < .05). Whether the shape of PTC is regular or not and whether there is micro-calcification in PTC and other ultrasonographic features, the size and location of the lesions and the age of the patient help make a preliminary prediction of local invasiveness before the operation. Postoperative detection of bFGF is helpful for further risk assessments of PTC.